CATEGORY ―INSTITUTIONAL DESIGN‖ AND ITS USE IN STUDYING OF TRANSITION ECONOMY - Пайманова, В. А. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2012)
The article is devoted to disclosure of the content of the category ―Institutional design‖ in case of economic system and its relation to the import and cultivation of institutions.